1998
DOI: 10.2535/ofaj1936.74.6_199
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Type Composition of Abdominal Muscles in Japanese Macaques(Macaca fuscata)

Abstract: Summary: The muscle fiber composition and cross-sectional area of muscle fiber types were investigated histochemically in the abdominal muscles (rectus abdominis muscle, obliquus externus abdominis muscle, obliquus internus abdominis muscle and transversus abdominis muscle) of three Japanese macaques (Macaca fuscata). Muscle fibers were classified into three fiber types (Type I, II A and II B) by myosin ATPase activity and succinate dehydrogenase activity. Each abdominal musde in Japanese macaques contained hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
2
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 24 publications
(24 reference statements)
1
2
0
Order By: Relevance
“…The rectus abdominis muscle of the Japanese monkey (Macaca fuscatta) has also been studied, in which 3 fiber types were observed, and fiber frequency showed the following relation: type IIB (FG) > I (SO) > IIA (FOG); Ito (1998). These results are similar to the data found in this study with the tufted capuchin monkey, in which FG fibers showed the highest frequency.…”
Section: Discussionsupporting
confidence: 86%
“…The rectus abdominis muscle of the Japanese monkey (Macaca fuscatta) has also been studied, in which 3 fiber types were observed, and fiber frequency showed the following relation: type IIB (FG) > I (SO) > IIA (FOG); Ito (1998). These results are similar to the data found in this study with the tufted capuchin monkey, in which FG fibers showed the highest frequency.…”
Section: Discussionsupporting
confidence: 86%
“…Muscle fibers are classified into type 1 fibers (slow-oxidative and fatigue-resistant), type 2A fibers (fast-oxidative-glycolytic and fatigue-resistant), and type 2B fibers (fast-glycolytic and fatigue-sensitive) ( Epstein, 1994 ). The diaphragm, which is the main inspiratory muscle, is composed of 80% fatigue-resistant fibers (55% type 1, 25% type 2A), while the rectus abdominis, the main expiratory muscle, is composed of 46% type 2B fibers ( Epstein, 1994 ; Ito, 1998 ). In sarcopenia, muscle atrophy is selectively observed in fast-twitch fibers ( Lexell, Taylor & Sjöström, 1988 ), suggesting that the diaphragm may be less atrophic and maintain its inspiratory muscle strength, while the rectus abdominis may be more prone to atrophy and loss of expiratory muscle strength.…”
Section: Discussionmentioning
confidence: 99%
“…Ito (1998) showed that fiber composition of the abdominal muscles (internal and external oblique muscles, transversus and rectus abdominis) of Japanese monkeys was similar: 26 % type I fiber, 22% type IIA fibers and 52% type IIB fibers. Augusto et al (2004) obtained similar results in C57BL6J rats.…”
Section: Discussionmentioning
confidence: 98%